Risk factors associated with osteonecrosis of femoral head after internal fixation of femoral neck fracture:a systematic review and meta-analysis - Xu, Jing-Li (BMC Musculoskelet Disord, 2019)
BACKGROUND: Although the risk factors associated with osteonecrosis of femoral head (ONFH) after internal fixation of femoral neck fracture (IFFNF) have been frequently reported, the results remain controversial. Therefore, its related risk factors were systematically evaluated and meta-classified in this study. METHODS: Literature on risk factors of ONFH caused by IFFNF was retrieved in PubMed, Embase and Cochrane Library due June 2019. Review Manager 5.3 software was applied to data synthesis, and Stata 13.0 software was adopted for analyses of publication bias and sensitivity. RESULTS: A total of 17 case-control studies with 2065 patients were included. The risk of ONFH after IF was 0.40-fold higher in patients with Garden III-IV FNF than that in patients with Garden I-II (OR: 0.40, 95%CI: 0.29–0.55). The risk of OFNH with retained IF was uplifted by 0.04 times (OR: 0.04, 95%CI: 0.02–0.07). There was nonsignificant relationship between gender and ONFH after IFFNF (OR: 1.27, 95%CI: 0.84–1.94). Moreover, ONFH after IFFNF presented no association with age (OR:1.66, 95%CI: 0.89–3.11), injury-operation interval (OR:1.29, 95%CI: 0.82–2.04), fracture reduction mode (OR:1.98, 95%CI: 0.92–4.26), preoperative traction (OR:1.69, 95%CI: 0.29–9.98) and mechanism of injury (OR:0.53, 95%CI: 0.06–4.83). Egger’s and Begg’s tests indicated a publication bias (P = 0.001). CONCLUSION: It was demonstrated that Garden classification and retained IF were important influencing factors of ONFH after IFFNF. Gender, age, injury-operation interval, fracture reduction mode, preoperative traction and the mechanism of ONFH were irrelevant to the complication.